The Effect of Corporate Social Responsibility Disclosure on Corporate Financial Performance - Thao, Duong Thi Thu; Le, Mai Thi (International Journal of Business, Economics and Management, 2019)
Corporate social responsibility (CSR) is gradually turning into a critical issue in business management. Over the decades, both theoretical and empirical literature were concentrated on studying the effect of CSR disclosure on corporate financial performance (CFP). However, the results have been ambiguous and inconsistent. The purpose of this paper is to examine the relationship between CSR disclosure and CFP in Vietnamese large listed firms on short-term and long-term profitability. We performed linear regressions on the sample data to investigate the effect of CSR disclosure on corporate financial performance. CSR disclosure is measured by using a disclosure index which consists of environmental, social, economic and legal aspects. For CFP, return on assets (ROA) and Tobin’s Q ratio were employed as measures of short-term and long-term profitability respectively. The results indicated in the short run, there is no significant relationship between CSR disclosure and corporate financial performance. However, in the long run, there was a positive significant relationship between CSR disclosure and corporate financial performance. The results are encouraging since it provides empirical evidence that Vietnamese firms can be both socially responsible and financially successful. It is expected to make Vietnamese firms become more aware of the significance of CSR practice.